CARACTER EDUCATION FROM CASSANDRA’S SCHIZOPHRENIA DEPICTED IN TOREY HAYDEN’S TWILIGHT CHILDREN - Suwono; Yudi Agus Setiawan (PROCEEDING AL GHAZALI International Conference, 2023)
The research entitled “Caracter Education from Cassandra’s Schizophrenia Depicted in Torey Hayden’s Twilight Children” is aimed to analyze the symptoms of schizophrenia which appear in a character named Cassandra. Descriptive qualitative method is used to analyze the data. The data source of this study was the novel which is analyzed by using psychoanalysis. There are steps done in analyzing the novel. The first is determining the novel which is going to be analyzed that is the novel Twilight Children and the second is obtaining the elements of the novels, such the narrations, utterances, attitudes and the characterization of Cassandra. The result, schizophrenia is known as incurable illness. All those data show Cassandra’s ways in overcoming her schizophrenia. The ways can be categorized into three points. Those three things are according to the two treatments for schizophrenia, family education and relationship, and individual psychotherapy